A STUDY OF THE MICROSTRUCTURE OF CdSe:Cu,Cl FILMS HEAT-TREATED IN VACUUM AND AIR IN CuCl2 VAPOR - Tuychibaev B.K; Yuldashev N.Kh (Western European Studies, 2025)
The article presents the results of X-ray diffraction and electron microscopic studies of films with various processing parameters. It is shown that with increasing substrate temperature from 250 to 400°C, the scattering angle of the texture axis increases, as does the proportion of the hexagonal modification, crystallite size, and coherent X-ray scattering regions. After annealing in air in the presence of CuCl2 (Tann = 300°C), the films obtained at Tn = 250°C undergo a reorientation of crystallites from the (111)k+(0002)r plane, parallel to the substrate plane, to through the plane
Keywords: Photosensitive film; CdSe:Cu; longitudinal photoconductivity